Pendidikan Anti Kekerasan Berwawasan Lingkungan - Abdullah Hadziq (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2018)
Abstract: Violence in education is not always about physical abuse but also ethics abuse. In Indonesia, violence tends to be unconciously accepted by most people. Learners are often treated ihumanity and they do not fight back. For instances, get push-up, kicked door, and other physical punishments are often seen by Indonesian. Yet, there some good educational systems in Indonesia that not using violence on learning. So, this study will elaborate concepts of nonviolence learning in Surya Mentari Natural Kindergarten in Surakarta. The research uses qualitatie method and phenomenological approach. In this research, I collect data by observation, documentation, and interview to be analyzed. This method also employs triangulation method data to make sure that it has been precise. The result shows that learning model in Natural Kindergarten Surya Mentari invites children getting outdoor class in rice field and nearby gardens because it is interesting learning resources for children.Â Keyword: Education,Violence, Environment